Interna????es em idosos por fraturas de f??mur: an??lise de indicadores demogr??ficos e gerenciais no estado de S??o Paulo de 2012 a 2017 - Vasconcelos, Elaine de (2019)
Following the aging process in the Department of Information of the Unified Health System (DATASUS), it is estimated that by the year 2050, the number of elderly will exceed the number of births. This new profile of the elderly population exposes challenges related to mobility, safety, autonomy, health and quality of life of the elderly, items that reflect the lack of strategic planning and public policies, appropriate to the elderly population. The objective was to analyze the demographic profile and management indicators of hospitalizations for diagnosis of femur fracture in elderly aged 60 years or older in SUS, considering data from the State of S??o Paulo and the period from 2012 to 2017. The analysis comprises three stages, being the first stage is the description of hospitalizations for femur fractures in the elderly, according to demographic variables (age and gender) in the state of S??o Paulo from 2012 to 2017; The second stage is the description of the average length of hospitalization for femur fracture in the elderly in the State of S??o Paulo and the third stage is the description of hospitalization for femur fracture in the elderly according to evolution and expenses in SUS. Data collection was performed through the Hospital Information System of the Unified Health System (SIH-SUS), considering the population estimate for the period between 2012 and 2017. The proportion of elderly in the State of S??o Paulo ranged from 11,73% in 2012 to 14.04% in 2017. There was an increase of 19.7% in the percentage of the elderly population in the state of S??o Paulo between 2012 and 2017. The proportion of elderly hospitalized in SUS in 2012 was equivalent to 24.97% in relation to the total hospitalizations of all other age groups. There was a 10.5% growth in the percentage of hospitalized elderly, and in 2017 reached the rate of 27.60%. In 2012 there were 5602 hospitalizations for femur fracture in people aged 80 years and over in the State of S??o Paulo, among which 466 resulted in death, representing 8.32% lethality. In this same age group, in 2017 there were 6,667 hospitalizations, of which 614 resulted in death, representing 9.12% of lethality. Considering the period studied, from 2012 to 2017, there was a positive variation of 10.71% of lethality. The results showed that the vulnerability of the elderly increases with advancing age, a factor that directly contributes to the onset of complications and diseases associated with advanced age and may progress to death.